90.7k views
20 votes
Colton solved an equation incorrectly, as shown below: Step 1: x − 13 = 26 Step 2: x = 26 − 13 Step 3: x = 39 Which statement best explains why Step 2 is incorrect in Colton’s solution?

User Yaquawa
by
4.9k points

2 Answers

5 votes

Answer:

'Cause he didn't use the inverse operation! ^^

Explanation:

Heres the correct way to solve it:

x-13=26

x=26+13

x=39

The correct way is to add 13 to both sides and not subtract.

--

Hope that this helped! Best wishes.

--

User Dervin Thunk
by
5.8k points
3 votes

Answer:

Step 2 explains why Colton's solution is incorrect because he subtracted 13 on both sides instead of adding it on both sides.

Hope it helps!

User Spacey
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.